UPAYA MENINGKATKAN KEMAMPUAN MOTORIK HALUS MELALUI METODE KOLASE PADA ANAK DIDIK KELOMPOK B TK PERTIWI GOTPUTUK KECAMATAN NGAWEN KABUPATEN BLORA - PAINEM, INEM (2015)
Abstract: Painem/A53I130015. Efforts To Increase Of Fine Motor Skills Through The Collage Method on Students of Group B Pertiwi Gotputuk Kindergarten. Publication of Scientific Article. Departemen Of Early Childhood Education, School of Teacher Trainning and Education, Muhammadiyah University of Surakarta. October, 2015. This research aims to improve fine motor skills of children through collage. This research is a classroom action research conducted in two cycles and each cycle outsmart conducted two meetings. The subjects of this study is children Group B TK Pertiwi Gotputuk District of Ngawen Blora totaling 15 children as recipients of actions, researcher and teacher colleagues as giving action. The data collected in this study is data about fine motor skills of children and data on teacher learning through collage. Both of these data were collected through observation. Data were analyzed children's fine motor skills with comparative analysis and data on teacher learning through activities collage analyzed by interactive analysis. The results of the analysis showed that the average prasiklus fine motor skills a child reaches 54% means that the new children's fine motor skills develop according to expectations. After the first cycle measures the average fine motor skills a child reaches 67%, which means that the child's fine motor skills are still developing according to expectations, but already there is an increase. After the second cycle measures the average fine motor skills children increased 86% means that children develop fine motor skills very baik. Kesimpulan of this study is that Efforts To Increase Of Fine Motor Skills Through The Collage Method on Students of Group B Pertiwi Gotputuk Kindergarten. Keywords : fine motor skills, Collage.